Foundations of Corporate Governance - Christophe Volonté (University of Basel, Center of Business and Economics (WWZ), 2012)
This paper outlines the foundations of corporate governance. The discussion includes a review on the modern corporation, transaction costs theory, agency costs theory, legal investor protection, investor protection by corporate governance and its various mechanisms, as well as an overview of the determinants of corporate governance.
Keywords: G30; G32; G34; K00; 330; Agency theory; Legal protection; Corporate goverance; Board of directors; Ownership; Corporate Governance; Board of Directors; Eigentümerstruktur; Transaktionskosten; Anlegerschutz; Prinzipal-Agent-Theorie